(untitled) (EDUCATION IN THE 21ST CENTURY, 2023)
The article touches upon the accreditation systems for higher education of the Republic of Armenia (RA) and the Republic of Kazakhstan (RK). Evolutions and development perspectives of the accreditation system of RA and RK have been analyzed, and a comparative analysis has been conducted. The development of accreditation systems for higher education in RA and RK is mainly in accordance with the principles of state educational policy and European standards and recommendations. The current model in both countries implies both institutional and program accreditation. Accreditation agencies in both countries are functionally independent. If the criteria and procedures for accreditation in the RA are approved at the level of the government, then in the RK it is the authority of accreditation agencies. We should also note the growth in the number of accreditation agencies of Kazakhstan and the larger volumes of both institutional and program accreditation in RK and abroad.